Immunohistochemical studies of αSMA in the epididymis of African four-toed Hedgehog (Atelerix albiventris) (2020)
The epididymis plays an important role in sperm maturation, storage, transport and in the secretion of enzymes and proteins into the tubular lumen. In this study, we examined the histology, microstereology and immunohistochemical localization of alpha smooth muscle (αSMA) in the three regions of the epididymis of the African four-toed hedgehog (Atelerix albiventris). Ten adult males were captured from the wild in Ibadan, Nigeria, between May and October, 2016. The animals were euthanized and the epididymis (caput, corpus and cauda regions) were retrieved and fixed in buffered neutral formalin ahead of the paraffin technique, following standard procedures. The duct of the epididymis was lined by pseudostratified columnar epithelium comprising basal, principal and apical cells as well as intraepithelial lymphocytes in proximity to basal cells. The principal cells, the major cells encountered within the epididymal epithelium of the animal, decreased in population from the caput to the cauda epididymidis while the apical cells were more abundant in the cauda epididymidis. Positive reactions to αSMA were observed in the peritubular muscular coat of the epididymal duct as well as blood vessels across the three regions of the epididymis with the caput and cauda epididymidis showing stronger positive reactions compared to the corpus epididymidis. This study demonstrated that the histology, microstereology as well as the cellular constituents of the epididymal duct of the Atelerix albiventris are similar to those of other mammals with a slight variation. It has also highlighted variation in the localization of αSMA across the regions of the epididymis of the animal.